Analisis misi dan rancangan lapan-IPB satellite (LISAT) untuk pemantauan kemandirian pangan - Mahmud Arifin Raimadoya; Bambang Hendro Trisasongko; Alinda Zain; Wahyudi Hasbi; Andi Tahir (Jurnal Ilmu Pertanian Indonesia, 2011)
LAPAN-IPB micro satellite (LISAT) is the first EBA (Experimental Based Application) planned to be launched in 2013. The technical schedule implementation includes Phase-1 (2010), Phase-2 (2011), Phase-3 (2012), and Launching/Phase-4 (2013). This research was targeted at the Phase-1 (MAD: Mission Analysis and Design), with priority on space segment and user segment. Goal of this research were three critical elements: (1) initial document of MRD (Mission Requirements Definition) as a reference for next LISAT phase (policy), (2) electronic Basic Ricefield Map (e-BARIM) at the test site in Subang regency, West Java (user segment), and (3) test flight of 3-channel optical sensor (LISAT-EM3) at the test site (space segment). The study was scheduled for gadu season rice crop of 2010, and most of the work completed, except for flight test that were experiencing delay for several times. Flight was re-scheduled from early July to September, but eventually conducted in early November. This was due to the complexity of coordination of many agencies involved: LAPAN I Pustekelegan (administration), TNI headquarters (security clearance), Theta System, Germany (line-CCD), IPB (area-CCD) and Deraya Air (charter aircraft).